Narrow spacing dual-wavelength fiber laser based on polarization dependent loss control - Ahmad, Harith; M. R. K., Soltanian; C. H., Pua; Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi (IEEE, 2013)
By controlling the polarization state of a simple ring erbium-doped fiber laser with photonics crystal fiber, polarization controller (PC) and tunable band-pass filter, this paper demonstrates stable operation of narrow spacing dual-wavelength fiber laser (DWFL). The flexibility of the tunable band-pass filter and PC allows the spacing tuning of the DWFL from 80 pm up to 600 pm. Such tuning ability offers flexibility in the application of DWFL, particularly in tunable microwave generation and radio over fiber. Throughout the experiment, the DWFL shows high power stability within 0.6 dB and wavelength shift of less than 10 pm. In addition to that, it also produces a narrow linewidth optical output of 3 pm with a high signal to noise ratio of more than 60 dB.